2021
DOI: 10.1186/s12893-021-01287-z
|View full text |Cite
|
Sign up to set email alerts
|

Urogenital fascia anatomy study in the inguinal region of 10 formalin-fixed cadavers: new understanding for laparoscopic inguinal hernia repair

Abstract: Purpose To investigate the urogenital fascia (UGF) anatomy in the inguinal region, to provide anatomical guidance for laparoscopic inguinal hernia repair (LIHR). Methods The anatomy was performed on 10 formalin-fixed cadavers. The peritoneum and its deeper fascial tissues were carefully dissected. Results The UGF’s bilateral superficial layer extended and ended in front of the abdominal aorta. At the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 16 publications
3
8
0
Order By: Relevance
“…In addition to the one and two-layer theories regarding Denonvilliers’ fascia, Ghareeb et al [ 9 ] proposed a “multilayer” theory based on an anatomical study. Combining the UGF theory reported in our previous study [ 12 ] and the findings of other reports in the literature, we believe that the first layer of “Denonvilliers’ layer” reported by Ghareeb et al [ 9 ] is the true Denonvilliers’ fascia and that the second and third layers represent the visceral layer of the UGF. This conclusion was reached because these two layers extend along the posterior wall of the urinary bladder and the ventral side of the seminal vesicles and prostate and densely adhere to Denonvilliers’ fascia at the caudal end of the prostate.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…In addition to the one and two-layer theories regarding Denonvilliers’ fascia, Ghareeb et al [ 9 ] proposed a “multilayer” theory based on an anatomical study. Combining the UGF theory reported in our previous study [ 12 ] and the findings of other reports in the literature, we believe that the first layer of “Denonvilliers’ layer” reported by Ghareeb et al [ 9 ] is the true Denonvilliers’ fascia and that the second and third layers represent the visceral layer of the UGF. This conclusion was reached because these two layers extend along the posterior wall of the urinary bladder and the ventral side of the seminal vesicles and prostate and densely adhere to Denonvilliers’ fascia at the caudal end of the prostate.…”
Section: Discussionsupporting
confidence: 82%
“…Except for the one layer and the two-layer theory, W. M. Ghareeb et al [9] carried out an anatomical study and detailed the "multilayer" theory of the Denonvilliers' fascia. Combining the UGF theory reported by our previous study [12] and comprehending the literature, we believed that the rst layer of the "Denonvilliers' layer" was narrated by W. M. Ghareeb et al [9] was the actual Denonvilliers' fascia. Yet the second and third layers should be the visceral layer of UGF since it extended along the posterior wall of the urinary bladder and the ventral side of the seminal vesicles and prostate and at the caudal of the prostate densely cohered to the Denonvilliers' fascia.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In the 5th week of human embryonic development, the cloacal side of the mesonephric duct sends ureteral buds to the dorsal side of the embryo and extends into the caudal end of the mesonephric ridge [ 42 , 46 ], inducing differentiation into the metanephrogenic tissue, i.e., the human permanent kidney. The above embryonic developmental process verifies that the renal fascia accompanies the development of the urogenital system to migrate to the pelvis, which is similar to the idea proposed by Muntean [ 50 ], Diarra [ 21 ] and Yi Li [ 41 ] through dissection. Yang [ 61 ] et al observed the continuation of the renal fascia into the pelvis and wrapped the ureter, reproductive vessels, and hypogastric nerves, calling it the urogenital–hypogastric sheath.…”
Section: Resultssupporting
confidence: 76%